Hall Current Effect of Magnetic-Optical-Elastic-Thermal-Diffusive Semiconductor Model during Electrons-Holes Excitation Processes - Abdulkafi M. Saeed; Kh. Lotfy; Alaa. A. El-Bary (Journal of Mathematics)
In this study, a novel model is introduced when the Hall effect associated with a strong magnetic field is taken into account when the electrons and holes interact in the processes of semiconductor material. The plasma-elastic-thermal waves are investigated in the context of diffusive processes during optical-generated transport processes. The variable of thermal conductivity is obtained during graduated temperature due to the thermal impact of fallen light. The governing equations of the novel model are investigated in a unidimensional (1D) way when the electronics and elastic deformations have occurred. The Laplace transforms are used to convert the main dimensionless physical fields according to the initial conditions into the Laplace domain. When certain thermal, mechanical, holes, and electronic conditions are used, the analytical solutions of the fundamental fields can be produced to the outer surface of the semiconductor medium. Mathematically, the Laplacian computational inversion algorithm with a numerical approximation is used to achieve the fundamental physical quantities numerically in the time domain. The influences of several parameters (thermal relaxation times, Hall impact, and thermal conductivity parameters) on thermal conditions, mechanical stress, holes charge carrier field, and carrier density are prescribed with the help of graphical diagrams that are discussed theoretically.